Independent dose calculations for commissioning, quality assurance and dose reconstruction of PBS proton therapy. (7th April 2015) - Meier, G; Besson, R; Nanz, A; Safai, S; Lomax, A J
Abstract Pencil beam scanning proton therapy allows the delivery of highly conformal dose distributions by delivering several thousand pencil beams. These beams have to be individually optimised and accurately delivered requiring a significant quality assurance workload. In this work we describe a toolkit for independent dose calculations developed at Paul Scherrer Institut which allows for dose reconstructions at several points in the treatment workflow. Quality assurance based on reconstructed dose distributions was shown to be favourable to pencil beam by pencil beam comparisons for the detection of delivery uncertainties and estimation of their effects. Furthermore the dose reconstructions were shown to have a sensitivity of the order of or higher than the measurements currently employed in the clinical verification procedures. The design of the independent dose calculation tool allows for a high modifiability of the dose calculation parameters (e.g. depth dose profiles, angular spatial distributions) allowing for a safe environment outside of the clinical treatment planning system for investigating the effect of such parameters on the resulting dose distributions and thus distinguishing between different contributions to measured dose deviations. The presented system could potentially reduce the amount of patient-specific quality assurance measurements which currently constitute a bottleneck in the clinical workflow.